Avaliação da cicatrização em anastomose de intestino delgado, com administração do quimioterápico fluorouracila no intra operatório : estudo experimental em ratos - Salomão Junior, Lauzamar Roge (2016)
It has been recognized that adjuvante treatment of gastrointestinal tract câncer determines adverse effects on wound healing. Objective: To evaluate the effects on the healing process of an anastomosis of small intestine loop of rats with intravenous administration of 5-fluorouracil during surgery. Methods: male Wistar rats were operated on (n = 24), with a section and posterior thin-walled suture of the small intestinal wall. Subsequently, the animals were divided into two groups: a) chemotherapy group (n = 12) and physiological solution group (n = 12), being injected respectively 5-fluorouracil and physiological saline solution during surgery. On the fourth and eighth postoperative days, twelve rats were sacrificed to obtain samples of the anastomotic segment, six of each group. The variables studied were: tissue hydroxyproline level, histological study with hematoxylin- eosin, and concentrations of collagen type I (picrosirius), type III (reticulin) and type IV (immunohistochemical). Results: Levels of hydroxyproline and tissue analysis by hematoxylin and eosin of type IV collagen fibers did not differ between groups. Analysis of the collagen type I fiber revealed differences in the chemotherapy group in the fourth postoperative day compared with the eighth postoperative day (102.78 ± 22.50 vs. 145 ± 32.12 p = 0.045). There was a difference between the global averages in the quantification of type III collagen fibers, per the groups, being higher in the physiological saline group (140.245±6.489 vs. 116.303±6.489 p=0.033). Conclusion: the intravenous administration of 5- fluorouracil performed simultaneously during anastomosis of small intestine and evaluated by the variables discussed, did not cause changes in the healing process.